Of Straws, Camels, Research Regulation, and IRBs. (July 2019) - Friesen, Phoebe; Redman, Barbara; Caplan, Arthur
Institutional review boards (IRBs) have become beleaguered by a growth in responsibilities related to research oversight in the past several decades. A number of regulatory bodies have appeared in response to these novel and complex responsibilities, seeking to respond to among other issues, conflicts of interest, new technologies, and the potential misuse of research findings. Here, we examine several examples of these novel regulatory bodies as well as a number of concerns related to them that have been largely unacknowledged. Evidence suggests that there can be disharmony and conflicts between these regulatory bodies and IRBs, a lack of clarity with regard to their roles and responsibilities, as well as shortcomings within these entities that, at times, look a lot like the worries that have long been raised in relation to IRBs. We offer a brief discussion of how some of these concerns might be ameliorated, either through a significant restructuring of the system of research oversight, or perhaps through smaller changes to these regulatory bodies.